E-LEARNING FOR IMPROVEMENT QUALITY OF THE INDONESIAN HUMAN RESOURCES - Rohani Jahja Widodo (Universitas Ahmad Dahlan, 2007)
This paper presents E-Learning (E-L) to support the Programs of Education and Training (E&T), Research and Development (R&D) for improvement quality of the Indonesian Human Resources (IQIHR). The programs of the IQIHR must be related with the modern Art, Science, Engineering and Technology (ASET). The prosperity of the Human Resources will be approached from prosperity approach which is mainly emphasized with three universes of aspects: Physical, Intellectual, Emotional and Spiritual (PIES) aspects. There are three basic requirements for developing these aspects: Material, Energy and Information (MEI). Social welfare and increase of life quality are desired output that must be attained from the MEI aspects. Current standard of living of human being should be reported as feedback information in the programs of the IQIHR. In global communication, developed countries and developing countries should build several attractive and sound symbiosis bridges, to prevent loss of universe balances. High quality of human resources as products of IQIHR activities, have social impacts not only in developed countries but also in developing countries. A new work force strategy without denying the existing of high quality of human resources is established by retooling the work forces, thus the challenges of social impacts could be answered wisely and would be bright opportunities to improve human standards of living.